TINJAUAN YURIDIS TENTANG ADAT PITI RAMBANG DAERAH SUMBA - Tollif Adih Pambudih; Hari Soeskandi (Gapenas Publisher, 2022)
Discussion about the Sumba regional custom, which custom is this In an era that is increasingly developing with many laws and increasingly globalization, Indonesia is famous for its various tribes and customs, from Sabang to Merauke, its cultural culture and also the different regional languages, so sometimes there is also a custom that forces its citizens to continue to follow customary rules, the custom is a marriage that requires a man to take or marry a woman, after the traditional ceremony is over, marrying or marrying the woman is not good according to some people, but instead of meeting a woman either on the street in front of the house or at the market, then the woman is immediately pulled and even carried to be brought to the man's house, even though it was without the knowledge of the female guardian, after arriving at the woman's house, the new woman was given know. That the child or family is living in a man's house is due to the piti ramban (forced marriage) custom. From the little picture above, the custom has violated various existing rules, namely human rights (human rights), marriage law, as well as criminal law and the laws that apply in Indonesia